Report of the Expert Group on Delineation of New Hill Areas - Planning Commission (Planning Commission, 1986)
The Planning Commission set up an Expert Group under the Chairmanship of Major General G.C. Agarwal, Surveyor General of India on 20.05.1986 to go into the question of Delineation of New Hill Areas in the Country keeping in view the recommendations of the Working Group on Hill Areas Development during the Seventh Five Year Plan [June 1985]. The Terms of reference of the Expert Group are as follows: Examine the criteria for delineation of areas recommended by the Working Group on Hill Areas during the Seventh Plan and evolve appropriate criteria for delineation of hill areas taking note of altitude, compactness, ecological vulnerability and such other factors as are deemed fit in conjunction with the criteria suggested by the Working Group.
Government of India Planning Commission
Government of India Planning Commission